STRATEGI PENGEMBANGAN OBJEK WISATA ALAM SUMBER SONGO SEBAGAI UPAYA PENINGKATAN KESEJAHTERAAN MASYARAKAT DI DESA JENGGOLO KECAMATAN KEPANJEN KABUPATEN MALANG - Khurnia Tryadissa Rachmadhani; Mifdal Zusron Alfaqi (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2022)
The purpose of this study was to describe the strategy for developing the Sumber Songo natural tourism object in Jenggolo Village, the implementation of the strategy for developing the Sumber Songo natural tourism object in Jenggolo Village, and the impact of developing the Sumber Songo natural tourism object for the welfare of the people of Jenggolo Village. This research uses a qualitative approach with a descriptive type. The collection of research data was carried out using observation, interview and documentation techniques. The results of this study found that the strategy for developing the Sumber Songo natural tourism object was called the master plan. The implementation of this strategy is manifested in the form of increasing land productivity by building supporting infrastructure for tourism and the economy. The impact of this development is the creation of jobs, an increase in income and ease of carrying out social functions